A serpiginous eruption. (15th November 2021) - Carey, S.; Salisbury, J.; Rudd, E.; Courtney, K.; Berovic, M.; Walsh, S.
Abstract : Click https://www.wileyhealthlearning.com/#/online-courses/94ca4cf8-e34a-4f08-ab96-34dc0c131358 for the corresponding questions to this CME article.